1998
DOI: 10.1079/pns19980052
|View full text |Cite
|
Sign up to set email alerts
|

Appetite, feeding behaviour and energy balance in human subjects

Abstract: Since the Second World War there has been a secular trend of increased overweight and obesity in societies where people have ad libitum access to Westem-type diets (Royal College of Physicians, 1983;Gregory et al. 1990;White et al. 1991; Department of Health, 1995). Over this time period the economic costs of obesity and the personal costs of being overweight (in terms of reduced quality of life, increased morbidity and mortality) have been well documented (Seidell, 1995). Throughout this period scientific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 92 publications
(111 reference statements)
8
41
0
Order By: Relevance
“…2 Given the cross-sectional nature of this survey, no direct conclusions can be drawn between diet composition (or energy density) and obesity or BMI in these children. The positive association of ED with EI is consistent with short-term experimental studies 9,19 showing that energy-dense diets induce high energy intakes, and is only partly explained by the 6 month age difference between groups. Children with a high energy requirement may preferentially choose energydense foods, which ful®l their metabolic needs within a limited eating capacity.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…2 Given the cross-sectional nature of this survey, no direct conclusions can be drawn between diet composition (or energy density) and obesity or BMI in these children. The positive association of ED with EI is consistent with short-term experimental studies 9,19 showing that energy-dense diets induce high energy intakes, and is only partly explained by the 6 month age difference between groups. Children with a high energy requirement may preferentially choose energydense foods, which ful®l their metabolic needs within a limited eating capacity.…”
Section: Discussionsupporting
confidence: 74%
“…6 For example, in a recent study that controlled for the potential effect of both macronutrient composition and palatability, Bell concluded that energy intake was driven by the energy density of the meals provided. 9 A series of investigations using covert manipulations of energy density and macronutrient composition 7,19,24 and general reviews of the issue 10,19 have arrived at similar conclusions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The extent to which weight gain occurs following ingestion of excess nutrients depends on what happens to such excesses once they enter the body. There is a clear relationship between the priority with which surplus nutrients are voided from the body through being metabolised and excreted, and the extent to which they are stored [10]. Excess carbohydrates are readily metabolised and excreted, and stores are minimal (in the form of glycogen in the liver and muscles).…”
Section: How Do Humans Deal With Nutrient Excesses?mentioning
confidence: 99%
“…Partly for this reason, it remains contentious whether humans are able to regulate their intake of different macronutrients [10][11][12]. There are, nonetheless, three sources of information that suggest that we can regulate the intake of specific nutrients.…”
Section: Do Humans Regulate To An Intake Target?mentioning
confidence: 99%